Nanobody-Directed Specific Degradation of Proteins by the 26S-Proteasome in Plants - Baudisch, Bianca; Pfort, Ingrid; Sorge, Eberhard; Conrad, Udo (Frontiers in Plant Science, 2018)
Here, we present data showing the directed degradation of target proteins recognized by a specific nanobody in transgenic plants. Green fluorescent protein was depleted by a chimeric nanobody fused to a distinct F-box domain, which enables protein degradation via the ubiquitin proteasome pathway. This technique could thus be used to knock out other proteins of interest in planta using specific, high-affinity binding proteins.